Genome-wide mapping of insertion sites essential for propagation of coxsackievirus A9 - Mebarki, Ayoub (My University, 2024)
Mutagenesis is crucial for understanding and harnessing genetic variation, providing a basis for evolutionary biology and experimental gene function studies. This thesis addresses the MuA transposase system, an effective species-non-specific transposition-based in vitro insertional mutagenesis strategy, intending to implement this system to generate a library of coxsackievirus A9 (CVA9) mutants. Like other members of the Picornaviridae family, CVA9 causes a variety of diseases such as hand-foot-and-mouth disease, respiratory maladies and even central nervous system infections. The lack of antiviral drugs and vaccines for this group of viruses necessitates further studies to advance our understanding of picornaviral pathogenesis and therapeutic targets. The project’s ultimate aim is to identify the genomic regions essential for the propagation of CVA9. This involves producing the required transposon mutagenesis system through the isolation, purification, and digestion of MuA plasmid DNA in order to assemble MuA-transposon complexes for mutagenesis. Furthermore, the thesis aims to check the functionality of the mutated pool of coxsackievirus A9 sequences and genome sequencing of viable virus mutants to map the mutated sites. MuA and CVA9 plasmids were transformed into competent cells and purified using several maxiprep kits, initially, the manufacturer's protocol was followed. However, modifications were introduced to increase DNA concentration. Restriction enzyme mapping, PCR amplification, and transfection into mammalian cells were conducted. Successful infection and GFP expression in T7-BSR cells confirmed the functionality of cloned constructs. This research establishes the fundamental components for using the Mu transposon system to create a library of mutated CVA9 (CVA9-eGFP vector) while highlighting the importance and impact of purification conditions, T7 RNA polymerase, primer design and transfection conditions in establishing a foundation for using the Mu transposition system in studying viral propagation. The findings lay the groundwork for future studies on picornavirus biology and the development of genetically modified viruses for pathogenicity studies and oncolytic virotherapy.
Keywords: Keywords: Mutagenesis, picornavirus, MuA transposase, plasmid, bacteriophage Mu, oncolytic virotherapy, reverse genetics.